EFFECT OF DIFFERENT DOSES OF PUMPKIN SEED OIL AS AN ANTI-INFLAMMATORY AND ANALGESIC ON MICE - yahya, N. Z. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
To evaluate the role of anti-inflammatory and analgesicof Iraqi pumpkin seed oil. The oil seed (25-100 mg / kg) were investigated using various experimental models for analgesic and anti-inflammatory benefit. Acetic acid and thermal induced models of pain were used to examine the anti-nociceptive property. Though models of oedema induced by carragenin were used to evaluate anti-inflammation. Results were reported from these studies that the extract prepared from Iraqi pumpkin seeds possess potential anti-inflammatory and analgesic activity when compared with standard drug Diclofenac. Even though all the concentrations showed varying degree of inflammatory and analgesic activity, 100mg/kg bw showed better anti inflammatory and analgesic activity